DIAGNOSTICS OF OIL-FILLED EQUIPMENT BY MEANS OF REGISTRATION OF PARTIAL DISCHARGES - G. Y. Kolesnikov (Современная наука и инновации)
One of the main tasks of diagnostics of oil-filled equipment is to measure the characteristics of partial discharges in isolation. In the subsequent planning of repairs, assessment of the degree of danger and maintainability of the defect, it becomes equally important to know the location of the source of partial discharges. The objectives of the experiments, the results of which are given in the article, are to determine the parameters of partial discharges in the controlled zones of transformers and to process the information received. Measurements were carried out using a device for recording partial discharges and determining defect zones of dielectric materials of high-voltage equipment. Thus, when conducting a comprehensive examination of transformers, it seems justified to combine the measurement of electrical characteristics of discharges with their acoustic location.